Data journalism and black-boxed data sets. (March 2019) - Lowrey, Wilson; Broussard, Ryan; Sherrill, Lindsey A.
This study explores the level of scrutiny data journalists from national, local, traditional and digital outlets apply to data sets and data categories, and reasons that scrutiny varies. The study applies a sociology of quantification framework that assumes a tendency for data categories to become "black-boxed, " or taken-for-granted and unquestioned. Results of in-depth interviews with 15 data journalists suggested these journalists were more concerned with data accessibility and ease of use than validity of data categories, though this varied across outlet size and level of story complexity.